Laboratorios creativos-caseros para la enseñanza de Físico Química, con los estudiantes de quinto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Morocho Lara, Cristopher Alejandro (2025)
This research examined the teaching of Physical Chemistry through creative home laboratories designed to promote student participation and interest. The objective was to propose creative home laboratories as a teaching strategy to facilitate learning in Physical Chemistry. The methodology was quantitative and non-experimental, using a field and bibliographic design at a descriptive level. Data were obtained via a survey administered to 21 fifth-semester students in the Pedagogy of Experimental Sciences (Chemistry and Biology) program. The questionnaire included 10 closed-ended, multiple-choice items. The study aimed to determine students’ perceptions of—and the benefits associated with—creative home laboratories as a teaching strategy in Physical Chemistry, particularly when supported by the Arcane teaching manual. Based on the results, we conclude that creative home laboratories focused on gas theory and thermodynamics are highly effective for stimulating interest in the subject and developing skills through hands-on activities that help students relate the abstract phenomena of Physical Chemistry to everyday situations, contributing to a more dynamic and inclusive educational model.